Food for all in 2020: can the world be fed without damaging the environment? - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (Cambridge University Press, 1996)
Approximately 780 million people world-wide are chronically undernourished, and past gains in food production have been associated with environmental problems, yet global demand for cereals is projected to increase by 56% and for meat by 74% between 1990 and 2020.The International Food Policy Research Institute has developed the view that every person in the world can have access to sufficient food to sustain a healthy and productive life, that malnutrition can be abolished, and that food can originate from efficient, effective, and low-cost food systems that are compatible with sustainable use of natural resources. Moreover, IFPRI has concluded that these conditions can be achieved by the year 2020, if the world commits itself to specified changes in behaviour, priorities, and policies. In order for these changes to occur, sustained action is needed in six areas: (1) strengthening the capacity of developing-country governments; (2) investing more in poor people; (3) accelerating agricultural productivity; (4) assuring sound management of natural resources; (5) developing competitive markets; and (6) expanding and realigning international development assistance. We have the knowledge and the capacity to meet the food needs of every person without damaging the environment. What is needed is political will and commitment on the part of all members of society to take the required action.